Using secondary additives to enhance the physicochemical properties of kaolinite - Moayedi, Hossein; Asadi, Afshin; Moayedi, Fatemeh; Kim Huat, Bujang; Kazemian, Sina (Academic Journals, 2011)
The adsorptions of various electrolytes namely; CH3COONa, H3PO4, Na2Sio3, Na2Co3, CaCl2, and Al2(SO4)3, onto kaolinite from aqueous solutions were investigated using zeta potential test. Based on zeta potential results, 36 different binders were designed using Na2Sio3 as well as H3PO4 as main stabilizers mixed with CaCl2 and Al2(SO4)3 as secondary additives at various electrolytes. Moreover, unconfined compressive strength (UCS) was used to find the undrained shear strength (USS) of treated kaolinite. From the experimental results, (i) pH strongly alters the zeta potential of kaolinite; (ii) The zeta potential of the kaolinite soils varied from 204.6 to -41.9 mV, based on the used chemical reagents as well as their concentration; (iii) Some of the electrolytes are able to change the interface charge from negative to positive for kaolinite; (iv) Thicker eiffuse double layer (EDL) as well as higher pH at the PZC resulted from the greater electrolyte concentration. Based on the results of zeta potential and pH observed from using different cationic species, those PZC which are more close to the soil pH are more succeptible to be chosen as the best reagent to stabilizing soil. Also, batch test results clearly showed the importance of using both CaCl2 and Al2(SO4)3 electrolytes as secondary additives in EK injection systems.